Disease Risk Comorbidity Index for Patients Receiving Haploidentical Allogeneic Hematopoietic Transplantation. (February 2021) - Mo, Xiao-Dong; Zhang, Xiao-Hui; Xu, Lan-Ping; Wang, Yu; Yan, Chen-Hua; Chen, Huan; Chen, Yu-Hong; Han, Wei; Wang, Feng-Rong; Wang, Jing-Zhi; Liu, Kai-Yan; Huang, Xiao-Jun
Abstract: We aimed to develop a disease risk comorbidity index (DRCI) based on disease risk index (DRI) and Hematopoietic Cell Transplantation-Specific Comorbidity Index (HCT-CI) in patients receiving haploidentical hematopoietic stem cell transplantation (haplo-HSCT). We identified the prognostic factors of disease-free survival (DFS) in a training subset ( n = 593), then assigned a weighted score using these factors to the remaining patients (validation subset; n = 296). The multivariable model identified two independent predictors of DFS: DRI and HCT-CI before transplantation. In this scoring system, we assigned a weighted score of 2 to very high-risk DRI, and assigned a weighted score of 1 to high-risk DRI and intermediate- and high-risk HCT-CI (i.e., haplo-DRCI). In the validation cohort, the three-year DFS rate was 65.2% (95% confidence interval (CI), 58.2%–72.2%), 55.8% (95% CI, 44.9%–66.7%), and 32.0% (95% CI, 5.8%–58.2%) for the low-, intermediate-, and high-risk group, respectively ( P = 0.005). Haplo-DRCI can also predict DFS in disease-specific subgroups, particularly in acute leukemia patients. Increasing score was also significantly predictive of increased relapse, increased non-relapse mortality (NRM), decreased DFS, and decreased overall survival (OS) in an independent historical cohort ( n = 526). These data confirmed that haplo-DRCI could effectively risk stratify haplo-HSCT recipients and provide a tool to better predict who will best benefit from haplo-HSCT.